Did the extension of the franchise increase the Liberal vote in Victorian Britain? Evidence from the Second Reform Act - Samuel Berlinski; Torun Dewan (Institute for Fiscal Studies (IFS), 2010)
We use evidence from the Second Reform Act, introduced in the United Kingdom in 1867, to analyze the impact on electoral outcomes of extending the vote to the unskilled urban population. By exploiting the sharp change in the electorate caused by franchise extension, we separate the effect of reform from that of underlying constituency level traits correlated with the voting population. Although we find that the franchise affected electoral competition and candidate selection, there is no evidence that relates Liberal electoral support to changes in the franchise rules. Our results are robust to various sources of endogeneity.
Keywords: 330; Politische Reform; Wahlrecht; Wahlverhalten; Liberale Partei; Zeitgeschichte; Großbritannien